World Christianities (c.1914 – c.2000), (ed.) Hugh McLeod: Cambridge 2006, The Cambridge History of Christianity, Cambridge University Press, s. 648 - Hanuš, Jiří (Dějiny – teorie – kritika, 2008)
Review